SN2017jgh: a high-cadence complete shock cooling light curve of a SN IIb with the Kepler telescope. Issue 3 (3rd August 2021) - Armstrong, P; Tucker, B E; Rest, A; Ridden-Harper, R; Zenati, Y; Piro, A L; Hinton, S; Lidman, C; Margheim, S; Narayan, G; Shaya, E; Garnavich, P; et al.
ABSTRACT: SN 2017jgh is a type IIb supernova discovered by Pan-STARRS during the C16/C17 campaigns of the Kepler / K2 mission. Here, we present the Kepler / K2 and ground based observations of SN 2017jgh, which captured the shock cooling of the progenitor shock breakout with an unprecedented cadence. This event presents a unique opportunity to investigate the progenitors of stripped envelope supernovae. By fitting analytical models to the SN 2017jgh light curve, we find that the progenitor of SN 2017jgh was likely a yellow supergiant with an envelope radius of 50\!-\!290 R_, and an envelope mass of 0\!-\!1.7 M_ . SN 2017jgh likely had a shock velocity of ∼7500−10 300 km s −1 . Additionally, we use the light curve of SN 2017jgh to investigate how early observations of the rise contribute to constraints on progenitor models. Fitting just the ground based observations, we find an envelope radius of 50\!-\!330 R_, an envelope mass of 0.3\!-\!1.7 M_ and a shock velocity of ∼9000−15 000 km s −1 . Without the rise, the explosion time cannot be well constrained that leads to a systematic offset in the velocity parameter and larger uncertainties in the mass and radius. Therefore, it is likely that progenitor property estimates through these models may have larger systematic uncertainties than previously calculated.